IMPACT OF INSECURITY ON SCHOOL ATTENDANCE OF JUNIOR SECONDARY SCHOOL STUDENTS IN MAIBUGURI METROPOLIS, BORNO STATE, NIGERIA - Abdullahi, U.; Atsua, T. G.; Amuda, B. G.; Habu, A. A. (Sokoto Educational Review, 2019)
The study addressed three questions, what is the level of school attendance under the crisis situation in Maiduguri metropolis? Are parents and teachers willing to send back their children to the affected schools? Does insecurity have a significant impact on attendance of school children? Impact of Insecurity Questionnaire (IIQ) was developed for the study. The alpha reliability of the questionnaire was .965. It was administered to 225 parents and teachers in 21 junior secondary schools in Maiduguri, Borno state that were affected in the activities of Boko Haram in the metropolis. The responses to the questionnaire were summarized using percentages. Chi-square was computed to test for differences in responses on the impact of insecurity on school attendance. The students were found the level of school attendance under the crisis situation in Maiduguri metropolis has been low but that of male students seems to be lower than that of female students. Parents and teachers were willing to send their children back to the affected schools. The impact of insecurity on school attendance was found to be significant.